Investigation of Household Debt through Multilevel Multivariate Analysis: Case of a Developing Country - Haq, Wajiha; Ismail, Noor Azina; Satar, NurulHuda Mohd (Journal of Reviews on Global Economics, 2018)
This study focuses on investigating the relationships between different socioeconomic and demographic characteristics and households’ debt decision and demand. We used six survey rounds of data from Pakistan household integrated expenditure survey (HIES) 2001 to 2014. HIES is a nationally representative data collected by Pakistan Bureau of Statistics. Multilevel models were used to investigate the relationship in which the data on households was nested in primary sampling units (PSUs) and PSUs were nested in provinces. The decision of taking household debt varies 22% at PSU level and 18% at provincial level due to unobserved variables. We found that households having higher financial assets, higher income and larger household sizes tend to have a higher percentage of debt. The amount of debt also increases with education and age. In the case of demand for debt, the variation is 12% at the provincial level. Literature studying household debt decision in Pakistan often ignore the geographical differences (region/province specific studies). Considering socioeconomic characteristics habituating the usage of credit is of countless importance in guiding policy design and interventions that aim to improve financial inclusion.